PENGARUH KEMAMPUAN BERBICARA SISWA DAN METODE PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR NOVEL - Oktaviandi Bertua Pardede (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Speaking skills and role-playing learning methods are variables used to determine their impact on student achievement. Students' learning achievement is expected to be known through discussion of novel subject matter where students can interpret their knowledge by speaking and interacting with the novel's contents through role-playing. The population of this study was students of VIII-C SMP Kemala Bhayangkari 1 Medan with a total of 24 research samples. One group pretest-posttest design was used to test the research hypothesis about the effect of the role-playing learning method on student achievement. On the other hand, this study also interprets the results of observations, questionnaires, and interviews as primary data to strengthen the analysis of the hypothesis testing obtained. In the end, this research shows that there are 27.8% of students do not master speaking skills with a total of 73.6% of students whose speaking skills need to be improved and only 26.4% of students who have speaking skills. The results of the study also illustrate that appearing in public places, asking questions when studying in class, and discussing lesson topics while studying in class are the 3 main factors that need to be optimized by students. The hypothesis test shows the value of sig > which means accepting H0 that there is no difference in the students' pretest and posttest scores so that the role-playing learning method has not had a different effect on student achievement.